Modeling antibiotic transport and mapping the environmental risk in the Marmara region by using geographical information systems (GIS) - Küçükdoğan, Arın. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2013., 2013)
As human population increases, livestock farming has become more intensive for several decades. Veterinary antibiotics (VAs) are one of the most widely preferred drugs for animal health and management. Since a considerable fraction of antibiotics is excreted in animal waste; antibiotics can affect both soil quality by leaching from manure to soil and water quality by transporting to surface waters via runoff following to application of animal waste as manure on agricultural lands. Due to the fact that released antibiotics can lead to toxic effects and development of antibiotic resistant bacteria in the environment, there has been an increased concern about the adverse impacts of these micro pollutants causing chemical pollution. The antibiotic concentrations were previously measured in the soil and manure samples collected from various agricultural lands of the Marmara Region of Turkey in the scope of a scientific project. The aim of this study is to create environmental risk maps belonging to the Marmara Region in terms of antibiotic transport by determining risky pasture lands where risk mitigation actions would be essential. First of all, Storm Water Management Model (SWMM) was applied to simulate runoff water quantity stemming from rainfall events and hydraulics in the study area, which is divided into manageable modeling units such as catchments and subcatchments having different hydrological and hydraulic characteristics via Geographical Information Systems (GIS). Secondly, the transport of previously analyzed antibiotics in the Marmara Region was investigated by using the exposure model supplied by National Institute of Public Health and the Environment in The Netherlands (RIVM). Finally, the environmental risk of antibiotic transport in the Marmara Region was mapped with the help of GIS techniques by developing a Multi-Criteria Decision Analysis (MCDA) approach for all pasture lands.
Keywords: Antibiotics -- Environmental aspects.; Water -- Pollution.